2021
DOI: 10.1186/s13052-021-01084-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal iron supplementation and newborn birth weight: a quantile regression analysis

Abstract: Objective Our study aimed to explore the association between maternal iron supplementation and newborn birth weight (BW) in Shaanxi Province using quantile regression (QR). Method The data used in this study were derived from a large cross-sectional survey of a population in Shaanxi Province, Northwest China. A total of 28,209 women and their infants were selected using a stratified multistage random sampling method. The effect of iron supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Our finding was consistent with some previous studies. A large cross-sectional study in China showed that iron supplementation was positively associated with birth weight after controlling some potential confounders 14 . National representative data from India also found that iron supplementation during pregnancy was inversely associated with LBW after adjusting for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was consistent with some previous studies. A large cross-sectional study in China showed that iron supplementation was positively associated with birth weight after controlling some potential confounders 14 . National representative data from India also found that iron supplementation during pregnancy was inversely associated with LBW after adjusting for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no association was found between Fe supplementation and neonatal morphometric parameters. However, Shi et al [51], in their study of women and newborns from singleton pregnancies, reported that Fe supplementation during pregnancy had an effect on increasing the birth weight of newborns, particularly in women with anemia. However, it is important that the supplementation is individually tailored, as the excessive intake of Fe may have negative effects on fetal development.…”
Section: Iron Concentration In Afterbirthmentioning
confidence: 98%
“…In a meta-analysis of 48 randomized controlled trials (RCTs) and 44 cohorts, it was found that prenatal iron supplementation was associated with higher birth weight and a lower risk of low birth weight (LBW) compared to no supplementation [6]. Several studies have found positive associations between iron supplementation [13], dietary iron intake [14][15][16], and iron concentration in blood [17], cord blood [18], and placenta [8], and neonatal anthropometric indicators such as body length [8,19,20], chest circumference [21], and head circumference [7,18]. Two systematic reviews [22,23] did not find any significant associations between iron supplementation (mostly combined with folic acid) and anthropometric indicators in infants, children, and adolescents.…”
Section: Introductionmentioning
confidence: 99%